Nitrite Oxidizer Activity and Community Are More Responsive Than Their Abundance to Ammonium-Based Fertilizer in an Agricultural Soil - Ouyang, Yang; Norton, Jeanette M. (Frontiers in Microbiology, 2020)
Autotrophic nitrification is mediated by ammonia oxidizing bacteria (AOB) or ammonia oxidizing archaea (AOA), and nitrite oxidizing bacteria (NOB). Mounting studies have examined the impact of nitrogen (N) fertilization on the dynamic and diversity of AOA and AOB, while we have limited information on the response of the activity, abundance, and diversity of NOB to N fertilization. We investigated the influence of organic and inorganic N fertilizers on soil NOB in silage corn field plots that received contrasting nitrogen (N) treatments: control (no additional N), ammonium sulfate (AS100 & 200 kg N ha-1), and compost (200 kg N ha-1). Nitrifying community was examined using a universal marker (16S rRNA gene), functional gene markers (AOB amoA and Nitrospira nxrB), and metagenomics. The overall nitrifying community was not altered after the first fertilization, but was significantly shifted by four-year repeated application of ammonium fertilizers. Nitrospira were the dominant NOB (> 99.7%) in our agricultural soil. Both community compositions of AOB and Nitrospira were significantly changed by ammonium fertilizers, but not by compost after four years of repeated applications. All nitrifiers, including comammox, were recovered in soil metagenomes based on a gene-targeted assembly, but their sequence counts were very low. Although N treatment did not affect the abundance of Nitrospira nxrB determined by quantitative real-time PCR, ammonium fertilizers significantly promoted rates of potential nitrite oxidation determined at 0.15 mM nitrite in soil slurries. Understanding the response of both ammonia oxidizers and nitrite oxidizers to N fertilization may initiate or improve strategies for mitigating potential environmental impacts of nitrate production in agricultural ecosystems.